Coupled Excited-State Dynamics in N-Substituted 2-Methoxy-9-Acridones - Gonzalez-Garcia, M. Carmen; Herrero-Foncubierta, Pilar; Castro, Silvia; Resa, Sandra; Alvarez-Pez, Jose M.; Miguel, Delia; Cuerva, Juan M.; Garcia-Fernandez, Emilio; Orte, Angel (Frontiers in Chemistry, 2019)
Fluorophores of the acridone family have been widely employed in many applications, such as DNA sequencing, the detection of biomolecules, and the monitoring of enzymatic systems, as well as being the bases of intracellular sensors and even antitumoral agents. They have been widely used in fluorescence imaging due to their excellent photophysical properties, in terms of quantum yield and stability. However, frequently, the fluorescence emission data from acridones are not easily interpretable due to complex excited-state dynamics. The formation of π-stacking aggregates and excimers and excited-state proton transfer (ESPT) reactions usually result in emission features that are dependent on the experimental conditions. Therefore, an in-depth understanding of the dynamics involved in the excited-state transients of these dyes is mandatory for their appropriate application. Herein, we synthesized and fully characterized different 2-methoxy-9-acridone dyes. Their transient fluorescence emission spectra exhibited a complex dynamic behavior that can be linked to several excited-state reactions. We performed a thorough study of the excited-state dynamics of these dyes by means of time-resolved fluorimetry supported by computational calculations. All this allowed us to establish a multistate kinetic scheme, involving an ESPT reaction coupled to an excimer formation process. We have unraveled the rich dynamics behind this complex behavior, which provides a better understanding of the excited states of these dyes.